Static and Intertemporal Household Decisions - Chiappori, Pierre-Andre; Mazzocco, Maurizio (Journal of Economic Literature, 2017)
We discuss the most popular static and dynamic models of household behavior. Our main objective is to explain which aspects of household decisions different models can account for. Using this insight, we describe testable implications, identification results, and estimation findings obtained in the literature. Particular attention is given to the ability of different models to answer various types of policy questions.